PELATIHAN MEMBUAT PORTOFOLIO DIGITAL MENGGUNAKAN GOOGLE SITES UNTUK KEPENTINGAN ASESMEN KOMPETENSI GURU SEKOLAH DASAR - Eko Kuntarto; Muhammad Sholeh (Aptekmas Jurnal Pengabdian pada Masyarakat, 2023)
Teacher competence is knowledge, skills, behavior that must be owned by teachers in the learning process takes place or in carrying out their duties. In the target school, namely SDN 198/I Muara Bulian, there are still teachers who have difficulty making digital portfolios as a means of assessing teacher competence. Teachers are still unfamiliar with various online media that can be used as a means of creating digital portfolios. For this reason, a solution is provided in the form of training to create a digital portfolio using Google Sites. This training can make it easier for teachers to create digital portfolios for the benefit of assessing the competence of elementary school teachers. This activity is carried out using the Project Based Learning model and interactive learning methods. Trainers and participants carry out discussions, questions and answers, analysis, studies, and end with a project. The stages of activity are: (1) preliminary survey; 2) training and guidance; (3) create a project. This training received a very good response from the target schools, especially the teachers who participated in the training. Teachers become more innovative and professionally competent; in this digital era it is also increasing as evidenced by their success in creating an attractive digital portfolio after the training.